1999
DOI: 10.1038/sj.bjc.6690170
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy with mTHPC and polyethylene glycol-derived mTHPC: a comparative study on human tumour xenografts

Abstract: SummaryThe photosensitizing properties of m-tetrahydroxyphenylchlorin (mTHPC) and polyethylene glycol-derivatized mTHPC (pegylated mTHPC) were compared in nude mice bearing human malignant mesothelioma, squamous cell carcinoma and adenocarcinoma xenografts. Laser light (20 J/cm 2 ) at 652 nm was delivered to the tumour (surface irradiance) and to an equal-sized area of the hind leg of the animals after i.p. administration of 0.1 mg/kg body weight mTHPC and an equimolar dose of pegylated mTHPC, respectively. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 19 publications
1
38
0
Order By: Relevance
“…In previously published work using m-THPC, a drug-light interval of 4 to 12 hours resulted in extensive skin and muscle necrosis (20,21), indicating a low tumor-to-normal tissue ratio at this early time point. In contrary, no obvious changes in normal tissues were observed at any drug-light interval when pegylated m-THPC was used (22). Results of our study clearly show much higher tumor-toskin ratios in spontaneous feline squamous cell carcinoma with the liposomal drug.…”
Section: Patientsupporting
confidence: 58%
“…In previously published work using m-THPC, a drug-light interval of 4 to 12 hours resulted in extensive skin and muscle necrosis (20,21), indicating a low tumor-to-normal tissue ratio at this early time point. In contrary, no obvious changes in normal tissues were observed at any drug-light interval when pegylated m-THPC was used (22). Results of our study clearly show much higher tumor-toskin ratios in spontaneous feline squamous cell carcinoma with the liposomal drug.…”
Section: Patientsupporting
confidence: 58%
“…Its feasibility in association with cytoreductive surgery has been shown in several clinical studies in this respect. However, the efficiency and tumour selectivity of PDT for MPM depends on the choice of the sensitizer and on the treatment conditions applied [4][5][6][7][9][10][11][12][13] . Photofrin and mTHPC were the sensitizers used for intracavitary PDT after resection in patients with MPM [4][5][6][7] .…”
Section: Discussionmentioning
confidence: 99%
“…Most of these experiments were performed on nude mice bearing human mesothelioma xenografts [8][9][10]14] or on tumour-free minipigs [13] and canines [11] . However, none of these models allows the assessment of PDT on MPM growing within the pleural cavity in an experimental setting.…”
mentioning
confidence: 99%
“…This has led to relevant morbidity after PDT of the chest cavity after surgery for pleural mesothelioma [1][2][3][4][5][6], even in the presence of new second generation sensitizers [7][8][9][10][11][12][13]. Several experimental studies focusing on PDT for mesothelioma have shown that enhanced tumor selectivity may be obtained by modulating treatment conditions [14][15][16][17][18] and by pegylation of the sensitizer [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Since previous work has shown that tissue concentration measurements of free and pegylated mTHPC performed by HPLC were of limited use for predicting the photodynamic activity in this model [15,19], we hypothesized that fluorescence signaling measurements by fluorescence microscopy might be well suited in this respect. Fluorescence signaling of free and pegylated mTHPC was analyzed in tumors and skin by use of fluorescence microscopy in order to assess the photosensitizer distribution in tumors and to measure the tumor to skin fluorescence intensity ratio for both mTHPC formulations.…”
Section: Introductionmentioning
confidence: 99%